Identifying a novel IRF3/circUHRF1/miR-1306-5p/ARL4C axis in pancreatic ductal adenocarcinoma progression. Issue 4 (16th February 2022) - Liu, Wei; Deng, Lisha; Xu, Anchun; Xiong, Xingcheng; Tao, Jing; Chang, Jian; Xu, Yiling; Zhou, Zhilin
ABSTRACT: Pancreatic ductal adenocarcinoma (PDAC) is considered one most aggressive and lethal cancer types worldwide. While its underlying mechanisms are still poorly understood. CircRNAs play essential roles in various biological progression, including PDAC. Here, our results found that circUHRF1 was highly expressed in PDAC tumor tissues compared with normal tissues. Next, Cell or animal models were constructed, CCK-8, cell colony, EdU, flow cytometry assay, transwell migration, and Western blot assays were applied. CircUHRF1 knockdown influenced PDAC cell proliferation, apoptosis, migration and EMT level in vitro, and tumor growth in vivo . Subsequently, bioinformatics analysis, AGO2-RIP, RNA pull-down, and dual-luciferase reporter assays were used to explore the downstream targets in PDAC progression. Our findings suggest that circUHRF1 regulated ARL4C expression to promote PDAC progression through sponging miR-1306-5p. The role of miR-1306-5p in PDAC cellular progression has been elucidated, and the expression association between miR-1306-5p and circUHRF1 or ARL4C in PDAC tissues was analyzed. Furthermore, circUHRF1 expression in PDAC cells could be transcriptionally regulated by IRF3. Collectively, our study demonstrated the role of IRF3/circUHRF1/miR-1306-5p/ARL4C axis in PDAC progression. Our results suggest that circUHRF1 is one promising diagnosis or therapeutic target for PDAC management. Abbreviations : CircRNA; Circular RNAPDAC; pancreatic ductal adenocarcinomaUHRF1; Ubiquitin-like with PHD and RING finger domain 1ARL4C; ADP Ribosylation Factor Like GTPase 4CRIP; RNA immunoprecipitationEDU; 5-Ethynyl-2ʹ-deoxyuridineEMT; epithelial to mesenchymal transitionAGO2; Argonaute RISC Catalytic Component 2CCK8; Cell counting Kit-8IRF3; Interferon Regulatory Factor 3